Pregnancy induced displacement of preexisting microchimeric cells in the absence of maternal B and T cells - Pham, Giang; Shao, Tzu-Yu; Kinder, Jeremy M.; Peng, Yanyan; Turner, Lucien H.; Way, Sing Sing (Frontiers in Immunology, 2024)
Bidirectional exchange of cells between mother and fetus occurs during pregnancy, and persistence of these genetically foreign cells establishes long-term microchimerism in both individuals after parturition. Since women can have multiple pregnancies, and all mothers were once daughters themselves, the microchimeric milieu in each woman could theoretically contain cells from a variety of origins, including from their own mothers as well as their babies from each pregnancy. Interestingly and in sharp contrast to this prediction, we recently showed preexisting populations of microchimeric cells are lost following pregnancy and associated with seeding of new fetal microchimeric cells. Complete loss of preexisting microchimeric cells in this context draws parallels to immunological rejection with synchronized elimination of cells and tissues that express defined discordant antigens. This perspective evaluates this provocative hypothesis regarding pregnancy induced rejection of microchimeric cells, including new experimental data comparing microchimerism levels in mice simultaneously lacking B and T cells before pregnancy, and after parturition with primary and secondary pregnancies.